Antidiarrhoea and toxicological evaluation of the leaf extract of Dissotis rotundifolia triana (Melastomataceae) - Okoto Pius E; Abere Tavs A; Agoreyo Freddy O (BMC, 2010)
Abstract Background The leaves of Dissotis rotundifolia are used ethnomedically across Africa without scientific basis or safety concerns. Determination of its phytochemical constituents, antimicrobial activity, effects on the gastrointestinal tract (GIT) as well as toxicological profile will provide supportive scientific evidence in favour of its continous usage. Method Chemical and chromatographic tests were employed in phytochemical investigations. Inhibitory activity against clinical strains of Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Salmonella typhi were compared with Gentamycin. Our report includes minimum inhibitory concentration (MIC) against the tested organisms. The effect of the ethanol extract on the motility of the GIT in mice using the charcoal plug method and castor oil induced diarrhoea in rats was evaluated. Toxicological evaluation was determined by administering 250 mg/kg and 500 mg/kg of extracts on male Wistar rats for 14 days with normal saline as control. The tissues of the kidneys, liver, heart and testes were examined. Results Phytochemical studies revealed the presence of alkaloids, saponin and cardiac glycosides. The crude ethanol extract and fractions inhibited the growth of E. coli, P. aeruginosa, S. aureus and S. typhi to varying extents. The degree of transition exhibited by the charcoal meal was dose-dependent. In the castor oil induced diarrhoea test, all the doses showed anti-spasmodic effects. The LD50 in mice was above 500 mg/kg body weight. Toxicological evaluation at 500 mg/kg showed increased cytoplasmic eosinophilia and densely stained nuclei of the liver, tubular necrosis of the kidney, presence of ill-defined testes with indistinct cell outlines and no remarkable changes in the heart. Conclusion Ethanol extracts of Dissotis rotundifolia have demonstrated antimicrobial activity against clinical strains of selected microorganisms. The plant showed potential for application in the treatment of diarrhoea, thereby justifying its usage across Africa. It also demonstrated toxicity in certain organs at the dose of 500 mg/kg, and it will be necessary to fully establish its safety profile.